Stabilization Strategy for Unstable First Order Linear Systems with Large Time Delay - del-Muro-Cuéllar, B.; Márquez-Rubio, J.F.; Velasco-Villa, M.; Alvarez-Ramirez, J. (IFAC Proceedings Volumes, 2010)
This work considers the problem of stabilization of a class of unstable first order linear systems subject to large input-output time delay. It is proposed a double output feedback one of then subject to time delay. Necessary and sufficient conditions are stated to guarantee the stability of proposed scheme based on two static gains. The stability conditions are derived by considering a discrete time approach, that under the assumption of a sampling time tending to zero, it is possible to infer the corresponding conditions for the continuous case.